FETHULLAH GÜLEN PORTRESİ - (:unkn) unknown (My University, 2016)
Bu çalışmada Fethullah Gülen'in Erzurum'dan başlayarak, Batı Anadolu ve ABD'ye kadar uzanan kişisel hayat serüveni ele alınarak, dini ve siyasi kimliğinin ve belirgin kişilik özelliklerinin oluşum ve değişim süreçleri anlaşılmaya çalışıldı. Osmanlı'nın tarihsel hafızasını taşıyan Erzurum'un, Cumhuriyet devriyle imtihanında kişiliği şekillenmeye başlayan Gülen'in, İzmir'de Nurcu hareketin bir parçası olarak gösterdiği faaliyetler ve zamanla geliştirdiği özgün yöntemler ele alındı. 1980'de Klasik Nurculuktan kopan Gülen Cemaati'nin güçlü bir dini cemaat, hatta Türkiye'nin ilk ulus-ötesi dinsel cemaati olmasını mümkün kılan koşullar anlaşılmaya çalışıldı. Gülen'in değişen zaman ve zemine uyum sağlama anlamında geliştirdiği söylem ve stratejiler irdelendi. Cemaatin içeride ve dışarıda ayrı söylemler geliştirmeye dayalı kültürünün barındırdığı etik ve siyasi meseleler ele alındı. Cemaatin diğer İslami çevreler ve Milli Görüş hareketiyle, bir bütün olarak İslamcılık'la meseleleri ortaya konuldu. Son olarak, son dönemde AKP ile yaşanan gerilimin nedenleri ve muhtemel sonuçlarına dair bazı gözlemler paylaşıldı. Cemaatin geleceğine dair kimi değerlendirmelere yer verildi.

In this study, Fethullah Gülen's personal life story which began in Erzurum and continued up to West Anatolia and U.S.A., have been handled with a recourse to his religious and political identity as well as his distinct personal features. In this respect, both Erzurum's exclusive role in terms of bearing the Ottoman's historical memory and Gülen's personality formed around the trial with the Republican period have been dealt along with his activities as a member of Nurcu movement and the specific methods that he developed in time. The conditions which rendered Nurcu movement as a powerful and the first trans-national religious community in Turkey, especially after its disengagement from the Classical Nurculuk in 1980, have been weighted up too. Gülen's discourses and strategies for adapting himself to the changing times and grounds have been analysed. The ethical and political issues that Nurcu movement reserved in its culture characterized by establishing different discourses in domestic and foreign grounds have been investigated. Nurcu movement's interactions with other Islamic circles, with the National Vision movement and its affairs with Islamism as a whole have been set forth. Eventually, some observations on the reasons underlying the tension between AKP and Nurcu movement and the possible results of this tension have been shared along with some evaluations about the future of this movement.
THE PORTRAIT OF FETHULLAH GÜLEN
Keywords: Din Bilimi